VARISCAN VEINS: RECORD OF FLUID CIRCULATION AND VARISCAN TECTONOTHERMAL EVENTS IN UPPER PALAEOZOIC LIMESTONES OF THE MORAVIAN KARST, CZECH REPUBLIC - Slobodnik M.; Muchez Ph.; Kral J.; Keppens E. (My University, 2006)
Numerous Variscan syntectonic calcite veins cross-cut Palaeozoic rocks in the Moravian Karst. A structural, petrographic and stable isotopic analysis of the calcite veins and a microthermometric study of fluid inclusions in these vein cements have been carried out to determine the origin of the Variscan fluids and their migration during burial and deformation. The isotopic parameters of white (older, more deformed) and rose (younger) calcites are: 87Sr/86Sr is between 0.7078 and 0.7082 (white) and 0.7086 (rose), δ18O is between +17.7 and +26.1 (white) and between +14.8 and +20.7 ‰ SMOW (rose), δ13C ranges from +0.1 to +2.5 (white) and from -0.3 to +1.6 ‰ V-PDB (rose). The isotopic signatures point to precipitation in an older fluid system buffered by the host rock (white calcites) and to an open, younger fluid-dominated system (rose calcites). Parent fluids (H2O-NaCl system) had salinities between 0.35 and 17.25 eq. wt % NaCl. The pressure-corrected and confined homogenization temperatures suggest formation of the calcite veins from a fluid with a temperature between 120 and 170 °C, a pressure of 300-880 bar at a depth between 2.1 and 3.2 km. The fluids were most likely confined to a particular sedimentary bed as a bed-scale fluid migration (white older calcite veins) or, later, to a pile of Palaeozoic sediments as a stratigraphically restricted fluid flow (rose younger calcite veins). The low temperatures and pressures during precipitation of calcites, which took place close to a peak of burial/deformation, confirm the distal position of the Moravian Karst region within the Variscan orogen.
Keywords: PALAEOZOIC; CALCITE; VEINS; SYNTECTONIC PROCESSES; FLUID DYNAMICS